PERKEMBANGAN STUDI ISLAM DI DUNIA BARAT - Rubila Rubila; Heriyanto Heriyanto; Prabias Supardi (Adisam Publisher, 2025)
Islam is a religion that has many points of view, some consider it a blessing, some consider it terror. In Islam, there are those who use it as a guide for behavior. Then there are those who force them to carry out God's commands, there are those who invite them to carry out His commands. Sometimes people think of it as synonymous with the harsh conditions in the Middle East, sometimes people think of it as synonymous with the soft conditions in the archipelago. Until now, Muslims are still experiencing development, in almost all parts of the world, including in Europe which is not close to the place where Islam first emerged and developed, there are groups of Muslims who live and settle in that area. Islam began to enter Europe centuries ago. It all started with the conquest of the country of Andalusia in 756 AD - 1492 AD on the Iberian Peninsula. Then it continued through Sicily and the conquest of the Balkan region carried out by the Ottoman Caliphate. The presence and development of Islam in Europe then continued from the massive immigration of Muslims in Islamic countries to Europe after the end of the second world war.